Shallow convective mixing promotes massive Noctiluca scintillans bloom in the northeastern Arabian Sea. (January 2019) - Sarma, V.V.S.S.; Patil, J.S.; Shankar, D.; Anil, A.C.
Abstract: The northeastern Arabian Sea (NEAS) experiences convective mixing during winter, but this mixing does not reach up to the silicicline, resulting in the limited supply of silicate (Si) compared to nitrate (N) and phosphate (P) to the mixed layer (ML) and formation of non-diatom blooms. The poleward advection of waters of low surface salinity by the West India Coastal Current (WICC) to the NEAS weakens the vertical mixing and reduces the Si input to the mixed layer, resulting in occurrence of Noctiluca scintillans blooms. The saturation of dissolved oxygen in the NEAS varied between 88 and 98%, suggesting N . scintillans blooms occur in oxic conditions. Enhanced cell abundance of N . scintillans was observed in the bloom region in the upper 10 m. Phytoplankton pigments data revealed higher contribution of Chlorophytes, Prasinophytes, Prymnesiophytes and Prochlorophytes in the bloom than non-bloom region. The isotopic composition of nitrogen and carbon of particulate organic matter indicated that natural and in situ processes contributed to both nutrients and organic carbon pool in the NEAS in supporting the massive occurrence of N . scintillans blooms than hitherto hypothesized to anthropogenic sources. This study further suggests that the effect of anthropogenic pollutants released into the NEAS from the mega-cities is limited to the neighbourhood of these cities and does not affect the open ocean. Highlights: Massive Noctiluca scintillans blooms occur through natural, in situ processes under oxic conditions. Noctiluca scintillans blooms are associated with weak vertical mixing and low silicate supply than nitrate and phosphate. Noctiluca scintillans blooms are not caused by pollutants released from the bordering countries.